2015
DOI: 10.1111/mmi.12939
|View full text |Cite
|
Sign up to set email alerts
|

Novel mechanisms of controlling the activities of the transcription factors Spo0A and ComA by the plasmid‐encoded quorum sensing regulators Rap60‐Phr60 in Bacillus subtilis

Abstract: Summary Bacillus subtilis and its closest relatives have multiple rap-phr quorum sensing gene pairs that coordinate a variety of physiological processes with population density. Extra-chromosomal rap-phr genes are also present on mobile genetic elements, yet relatively little is known about their function. In this work, we demonstrate that Rap60-Phr60 from plasmid pTA1060 coordinates a variety of biological processes with population density including sporulation, cannibalism, biofilm formation and genetic comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 71 publications
1
47
0
Order By: Relevance
“…We show that the repressor and its antirepressor preferentially form dimers in solution and that complex formation occurs in a 1:1 stoichiometry that disrupts DNA binding of the repressor protein through obscuring the DNA-binding domain of the repressor. Unlike the plasmid-encoded Rap60, which presumably inactivates ComA activity by occluding its interaction with the RNA polymerase (26), inactivation of the Rco repressor by Rap LS20 resembles that of RapC, -F, and -H, which prevent DNA binding of ComA, which, however, is an activator, rather than a repressor, like Rco. Structural analysis of the RapF-ComA interaction showed that the N-terminal 3-helix bundle of RapF captures the helix-turnhelix-containing domain of ComA and thereby prevents binding of ComA to its target promoters (8).…”
Section: Discussionmentioning
confidence: 98%
“…We show that the repressor and its antirepressor preferentially form dimers in solution and that complex formation occurs in a 1:1 stoichiometry that disrupts DNA binding of the repressor protein through obscuring the DNA-binding domain of the repressor. Unlike the plasmid-encoded Rap60, which presumably inactivates ComA activity by occluding its interaction with the RNA polymerase (26), inactivation of the Rco repressor by Rap LS20 resembles that of RapC, -F, and -H, which prevent DNA binding of ComA, which, however, is an activator, rather than a repressor, like Rco. Structural analysis of the RapF-ComA interaction showed that the N-terminal 3-helix bundle of RapF captures the helix-turnhelix-containing domain of ComA and thereby prevents binding of ComA to its target promoters (8).…”
Section: Discussionmentioning
confidence: 98%
“…RapF blocks comA binding to DNA through direct competition for the DNA binding domain [27]. In contrast, Rap60 does not block ComA DNA binding but prevents the DNA-bound ComA from activating transcription [46]. …”
Section: Discussionmentioning
confidence: 99%
“…Clones were verified by DNA sequencing (UMASS Core Facility). Plasmid DNA was linearized by digestion with NcoI restriction enzyme (NEB) and transformed into B. subtilis strain JH642 by a two-step procedure described by Boguslawski et al (50), and the strain was plated on LB solid medium with neomycin.…”
Section: Methodsmentioning
confidence: 99%
“…Liquid cultures were grown in S7 defined minimal medium salts (45) containing 50 mM 4-morpholinepropanesulfonic acid instead of 100 mM (S7 50 ) and supplemented with 1% glucose, 0.1% glutamate, and the following trace metals: 2 M MgCl 2 , 0.7 M CaCl 2 , 50 M MnCl 2 , 1 M ZnCl 2 , 1 g/ml of thiamine, and 5 M FeCl 3 . Solid medium plates contained Spizizen salts (46) supplemented with 1% glucose and 0.1% glutamate.…”
Section: Methodsmentioning
confidence: 99%